Brain monitoring in adult and pediatric ECMO patients: the importance of early and late assessments - Lorusso, Roberto; Taccone, Fabio S; Belliato, Mirko; Delnoij, Thijs; Zanatta, Paolo; Cvetkovic, Mirjana; Davidson, Mark; Belohlavek, Jan; Matta, Nashwa; Davis, Carl; Ijsselstijn, Hanneke; Mueller, Thomas; et al. (Minerva anestesiologica, 2017)
Monitoring brain integrity and neurocognitive function is a new and important target for the management of a patient treated with extracorporeal membrane oxygenation (ECMO), in particular because of the increasing awareness of cerebral abnormalities that may potentially occur in this setting. Continuous regular monitoring, as well as repeated assessment for cerebral complications has become an essential element of the ECMO patient management. Besides well-known complications, like bleeding, ischemic stroke, seizures, and brain hypoperfusion, other less defined yet relevant injury and clinical manifestations are increasingly reported and impacting on ECMO patient prognosis at short term. Furthermore, it is becoming more evident that neurologic complication may not occur only in the early phase. Indeed, other potential adverse events related to the long-term neurocognitive function have been also recently documented either in children or adult ECMO patients. Despite increasing awareness of these aspects, generally accepted protocols and clinical management strategies in this respect are still lacking. Current means to monitor brain perfusion or detecting ongoing cerebral tissue injury are rather limited, and most techniques provide indirect or post-insult recognition of irreversible tissue injury. Continuous monitoring of brain perfusion, serial assessment of brain-derived serum biomarkers, timely neuro-imaging, and post-discharge counselling for neurocognitive dysfunction, particularly in pediatric patients, are novel pathways focusing on neurologic assessment with important implications in daily practice to assess brain function and integrity not only during the ECMO-related hospitalization, but also at long-term to re-evaluate the neuropsychological integrity, although well designed studies will be necessary to elucidate the cost-effectiveness of these management strategies.
Keywords: intraoperační neurofyziologická monitorace; Brain; mozek; mimotělní membránová oxygenace; Time Factors; Extracorporeal Membrane Oxygenation; Humans; lidé; časové faktory; Intraoperative Neurophysiological Monitoring